1993
DOI: 10.1128/aem.59.1.129-133.1993
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation of Woody Legumes with Selected Arbuscular Mycorrhizal Fungi and Rhizobia To Recover Desertified Mediterranean Ecosystems

Abstract: Revegetation strategies, either for reclamation or for rehabilitation, are being used to recover desertified ecosystems. Woody legumes are recognized as species that are useful for revegetation of water-deficient, low-nutrient environments because of their ability to form symbiotic associations with rhizobial bacteria and mycorrhizal fungi, which improve nutrient acquisition and help plants to become established and cope with stress situations. A range of woody legumes used in revegetation programs, particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1
9

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(64 citation statements)
references
References 19 publications
4
50
1
9
Order By: Relevance
“…Several studies have demonstrated that rhizobial inoculation can increase various components of plant performance. Examples include the yield of cultivated legumes (Young & Mytton, 1983;Bergersen, 1987;Thies et al, 1991), seedling survival and growth in revegetation projects (Herrera et al, 1993;Jha et al, 1995), and the lifetime reproductive success of Amphicarpaea bracteata (L.) Fernald in a natural habitat in eastern North America not previously occupied by this species (Parker, 1995). A second prediction, from assumptions (1) and (2) together, is that introduced legume populations may occasionally go extinct if inoculated rhizobia fail to survive due to competition from indigenous soil organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that rhizobial inoculation can increase various components of plant performance. Examples include the yield of cultivated legumes (Young & Mytton, 1983;Bergersen, 1987;Thies et al, 1991), seedling survival and growth in revegetation projects (Herrera et al, 1993;Jha et al, 1995), and the lifetime reproductive success of Amphicarpaea bracteata (L.) Fernald in a natural habitat in eastern North America not previously occupied by this species (Parker, 1995). A second prediction, from assumptions (1) and (2) together, is that introduced legume populations may occasionally go extinct if inoculated rhizobia fail to survive due to competition from indigenous soil organisms.…”
Section: Discussionmentioning
confidence: 99%
“…This process is physically mediated by mycorrhizal mycelia and glomalin, a glycoprotein of the hyphal wall (Miller & Jastrow 2000). Thus, the larger mycorrhizal mycelia associated with nurse species have an important effect in soil stabilization, which benefit species recruitment and accelerates succession in drylands and alpine ecosystems (Herrera, Salamanca & Barea 1993;Carrillo-Garc ıa et al 1999;Requena et al 2001;Ouahmane et al 2006;Casanova-Katny et al 2011;Duponnois et al 2011). In addition, soil aggregates contain water and nutritional resources that can protect micro-organisms from extreme conditions and affect microbial enzymatic activity (Six et al 2006;Bach & Hofmockel 2014).…”
Section: Soil Stabilizationmentioning
confidence: 99%
“…However, because many legume invasions derive from plants introduced for forestry or ornamental purposes, we cannot exclude the possibility that compatible rhizobial symbionts were co-introduced with their legume-hosts. Several studies have demonstrated that rhizobial inoculation can increase the yield of cultivated legumes (Bagyaraj et al, 1979;Young & Mytton, 1983) and seedling survival and growth in revegetation projects (Herrera et al, 1993;Rodríguez-Echeverría & Pérez-Fernández, 2005).…”
Section: Conclusion and Priorities For Future Workmentioning
confidence: 99%